2019
DOI: 10.1172/jci.insight.128241
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils downregulate lung alloimmunity by decreasing TCR signal transduction

Abstract: It has been demonstrated by us as well as others that eosinophils may alter their phenotype and function based on the local environment (7, 9, 10). Since costimulation plays a critical role in T cell cytokine production and environmental polarization (11, 12), we examined the possibility that eosinophils may lose their tolerogenic properties in the absence of CSB immunosuppression. Cytokine expression was examined in BALB/c (H2 d) lung allografts transplanted into fully MHC-mismatched C57BL/6 (B6) (H2 b) recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 52 publications
(56 reference statements)
8
41
1
Order By: Relevance
“…Interestingly, eosinophil depletion did not ameliorate rejection but actually prevented co‐stimulatory blockade (CSB)‐mediated graft acceptance and accentuated rejection in the absence of immunosuppression (Figure ). Unlike previous reports, which demonstrated an association of Th2 cytokines with the tolerance, we demonstrated that both CSB‐treated accepting as well nonimmunosuppressed rejecting grafts demonstrate a Th1 polarized microenvironment . This was marked by increased expression of IFN‐γ and TNF‐α without significant impact on Th2‐associated cytokines such as IL‐4, GM‐CSF, and IL‐33 .…”
Section: Eosinophils In Lung Transplantationcontrasting
confidence: 88%
See 3 more Smart Citations
“…Interestingly, eosinophil depletion did not ameliorate rejection but actually prevented co‐stimulatory blockade (CSB)‐mediated graft acceptance and accentuated rejection in the absence of immunosuppression (Figure ). Unlike previous reports, which demonstrated an association of Th2 cytokines with the tolerance, we demonstrated that both CSB‐treated accepting as well nonimmunosuppressed rejecting grafts demonstrate a Th1 polarized microenvironment . This was marked by increased expression of IFN‐γ and TNF‐α without significant impact on Th2‐associated cytokines such as IL‐4, GM‐CSF, and IL‐33 .…”
Section: Eosinophils In Lung Transplantationcontrasting
confidence: 88%
“…Our observation supports the unique role of pro‐inflammatory mediators in promoting lung allograft tolerance and reaffirms the uniqueness of lung‐specific immune responses . In line with Th1 polarization of the lung allograft microenvironment, eosinophils from both accepting and rejecting lung grafts were polarized to a Th1 (or E1)‐like phenotype . The Th1 signature of the lung allograft eosinophil differs from the Th2 (or E2)‐type associated with asthma and allergic inflammation …”
Section: Eosinophils In Lung Transplantationsupporting
confidence: 81%
See 2 more Smart Citations
“…logical properties of the lungs. Here, eosinophils form PD1-PDL1-dependent synapses with alloreactive T cells which results in the dissociation of the TCR-CD3 + complex 99. Some lung transplant patients receive indiscriminate T cell depletion strategies based on observations in other transplanted organs where memory T cells in particular are harmful to the allografts.…”
mentioning
confidence: 99%